Common Fixed Points for Maps on Topological Vector Space Valued Cone Metric Spaces - Ismat Beg; Akbar Azam; Muhammad Arshad (International Journal of Mathematics and Mathematical Sciences)
We introduced a notion of topological vector space valued cone metric space and obtained some common fixed point results. Our results generalize some recent results in the literature.